ترکہ نبوی ﷺ۔ ایک تحقیقی مطالعہ: Inheritance of Prophetﷺ: A Research Study - Dr. Hafiz Saeed ur Rehman (Al Manhal Research Journal, 2023)
To live, every person earns his wealth, some of which he spends during his life and some of which he has at the time of death. The wealth that a person leaves at the time of death is called Tarkah (Inheritance). This wealth is divided among the heirs in a certain proportion. It is very important to know that the case of the Prophets is different from that of their Ummahs in the chapter on Inheritance. At the time of death, whatever the prophets have is considered charity and the heirs cannot divide it among themselves. The true Inheritance of the prophets is their knowledge. According to the Prophet (peace be upon him), the prophets do not make anyone inherit worldly wealth, but the inheritance of the prophets is knowledge. There is much wisdom mentioned by scholars about not dividing the Inheritance of the Prophets. Some of the items used by the Messenger of Allah ﷺ were donated by him himself during his lifetime and those that were left were given as charity after his departure. There was a mule, weapons, and some household items in his Inheritance. The lands that were owned by the Prophet ﷺ were given in charity during his blessed life. A detailed discussion about the same will be discussed in the article under review.